Financialization, digital technology and income inequality - Mohd Daud, Siti Nurazira; Ahmad, Abd Halim; Wan Ngah, Wan Azman Saini (Taylor and Francis, 2021)
This paper investigates the impact of digital technology on the relationship between financialization and income inequality of 54 countries from 2010 to 2015. The results show that financialization and digital technology widen the income inequality gap. Therefore, policies should be centred primarily on eliminating obstacles and developing innovative products that focus on solutions to the low-income consumer problem and those who have been marginalized.